Want to lose weight? Don't count those steps. Issue 8 (August 2017) - Lyon, Corey
Abstract : N/A: Jakicic JM, Davis KK, Rogers RJ, King WC, Marcus MD, Helsel D, et al. Effect of wearable technology combined with a lifestyle intervention on long‐term weight loss: the IDEA randomized clinical trial. JAMA . 2016; 316(11):1161–1171. Erratum in: JAMA . 2016; 316(14):1498.